Upaya Mewujudkan Sekolah Inkusif: Sekolah Ramah Anak Dalam Implementasi Kurikulum Merdeka di Sekolah Dasar - Surtini Surtini; Nenden Ineu Herawati (CV. Alim's Publishing, 2024)
Every Indonesian citizen has the right to education, including those with special needs. Changes in the curriculum, tailored to the evolving times and the needs of students, make the curriculum inherently dynamic. The implementation of the Merdeka Curriculum is an effort to improve the quality of education in Indonesia in order to face the continuously evolving challenges of the times. This article aims to examine efforts to create child-friendly schools within the implementation of the Merdeka Curriculum in Indonesia. The approach used in data analysis is a qualitative approach. Realizing child-friendly schools within the framework of the Merdeka Curriculum requires the consistent and comprehensive application of the eight National Education Standards. This involves conducting initial evaluations of school infrastructure, teacher competencies, and student needs to identify areas that need improvement in order to support inclusive education. Regular monitoring and evaluation of the implementation of inclusive education are necessary to ensure its effectiveness and to make the required improvements.